REPRESENTASI KECEMASAN EKSISTENSIAL DALAM PUISI-PUISI SAPARDI DJOKO DAMONO - Masnita Massaguni; Budi Hartono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to describe the representation of existential anxiety in three poems by Sapardi Djoko Damono, namely Aku Ingin, Hujan Bulan Juni, and Pada Suatu Hari Nanti, through the psychoanalytic perspective of Sigmund Freud. This research employed a qualitative descriptive method with a literary psychology approach. The primary data consisted of lines, phrases, and symbolic expressions in the poems that indicate existential anxiety, psychic conflict, and defense mechanisms. Data were collected through close reading and note-taking techniques, then analyzed using data reduction, classification, interpretation, and conclusion drawing. The findings reveal that existential anxiety in Sapardi’s poems is represented through symbols of transformation, silence, deferred expression, and awareness of human finitude. In Aku Ingin, anxiety emerges through the symbolic transformation of wood into ash and clouds into rain as metaphors of loss and impermanence. In Hujan Bulan Juni, anxiety is reflected through emotional restraint and repression represented by delayed rain imagery. Meanwhile, Pada Suatu Hari Nanti demonstrates acceptance of death as a form of sublimation of existential fear. From Freud’s psychoanalytic framework, the ego appears dominant in regulating the affective impulses of the id through symbolic sublimation. This study shows that Sapardi’s poetic simplicity contains profound psychological complexity and contributes to expanding literary psychology studies in modern Indonesian poetry.